Corrigendum to "On time-varying factor models: Estimation and testing" [J. Econometrics 198 (2017) 84-101] - SU, Liangjun (Institutional Knowledge at Singapore Management University, 2020)
We note that Su and Wang (2017, On Time-varying Factor Models: Estimation and Testing, Journal of Econometrics 198, 84-101) ignore the bias terms when estimating the time-varying factor models. In this note, we correct the theoretical results on the estimation of time-varying factor models. The asymptotic results for testing the correct speciﬁcation of time invariant factor loadings are not aﬀected.